Intersecting challenges: Cancer caregivers’ experiences during COVID-19 - Charlotte R. Weiss; Rachel Johnson-Koenke; Karen B. Hirschman (Palliative Care and Social Practice)
Background: The COVID-19 pandemic introduced a landscape that contributed to many unknowns and unmet needs among cancer family caregivers and their care recipients. Aim: This secondary analysis qualitative study aimed to explore cancer family caregiver narratives for the societal and institutional contexts of caring for a person with advanced cancer during the early years of COVID-19. Design: Narrative inquiry was used in the parent study to co-create caregiver narratives. Methods: Narrative thematic analysis was used to identify themes of COVID-19 from five cancer caregiver narratives. Results: Thematic threads of COVID-19 were identified as short stories of tension woven throughout the caregiver narratives: advocacy for quality healthcare, the need to protect their person from the virus and medical/institutional disregard, financial strain, lack of social support, and the long goodbye. The findings further illustrate how COVID-19 and cancer intersect to influence a caregiver’s healthcare experience and well-being. Conclusion: Family-centered care strategies and policy changes are needed to better meet the complex needs of cancer caregivers during a pandemic and beyond.